2002
DOI: 10.2214/ajr.178.4.1780959
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Echoplanar MR Imaging of the Salivary Glands

Abstract: Diffusion-weighted echoplanar MR imaging may reveal diseased states of the salivary glands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
93
2
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 6 publications
8
93
2
5
Order By: Relevance
“…Many earlier studies employing ADC measurement have used the linear regression model and various sets of gradient b factors [6][7][8][9][10][11][12][13][14][15][16]18,19 . This model was also applied in this study, and three sets of gradient b factors (0 and 1000 sec/mm 2 , 500 and 1000 sec/mm 2 , and all b factors for WLR fit) were compared.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many earlier studies employing ADC measurement have used the linear regression model and various sets of gradient b factors [6][7][8][9][10][11][12][13][14][15][16]18,19 . This model was also applied in this study, and three sets of gradient b factors (0 and 1000 sec/mm 2 , 500 and 1000 sec/mm 2 , and all b factors for WLR fit) were compared.…”
Section: Discussionmentioning
confidence: 99%
“…The mobility of water molecules in fluid is freer than that in solid biological tissues, and the ADC values of cysts are higher than those of benign or malignant tumors 8,9,12 . On the other hand, the histopathological characteristics of malignant tumors such as enlarged nuclei, hyper-chromatism, and hypercellularity, reduce the extracellular matrix and the diffusion space of water molecules [7][8][9][11][12][13]15,16,18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, DWI has also been discussed as a way forward in the differentiation of benign and malignant tumors originating in musculoskeletal tissue 7,26) . DWI studies involving the knee joint 12) and salivary gland 21) have been also reported. However, to the best of our knowledge, there have been no reports on the use of DWI in the diagnosis of the temporomandibular joint diseases.…”
Section: Introductionmentioning
confidence: 99%